Use of inundated lakeshore vegetation by Cichlids for reproduction in Lake Kinneret (Israel) - Dabid Cummings; Avital Gsith (Frontiers in Marine Science, 2015)
The collapse of the Sarotherodon galillaeus fishery in Lake Kinneret, from a mean annual catch of ~300 tons, to less than 10 tons in 2008 may indicate an imbalance between reproduction and mortality of the species. One possible reason is shortage of suitable reproduction grounds at low water levels. This study was aimed at understanding the reproduction site preferences of the Cichlids in Lake Kinneret. Sites around the entire lake, representing both open shores and protected lagoons were surveyed in spring and summer of 2012, 2013 and 2014. The number of cichlid nests and environmental factors (water depth, water temperature, presence/absence of inundated vegetation and its density) were recorded along transects running perpendicular to the water line. Peak reproduction activity for S. galillaeus and Oreochromis aureus were recorded from April to June in all sites. Nest distribution varied between stations and between transects, with densities ranging from zero to over a hundred nests in 100 m2. reproduction took place in shallow water-mostly from 0.25 m to 1.5 m; no nests were observed in water deeper than 2 m. Lagoon sites had much higher reproduction activity than did the open shore sites. In the open shore sites, areas with moderate or light density of inundated vegetation were preferred over areas with no vegetation. Regression or poison type generalized linear models were employed to demonstrate that the different habitat types (lagoon vs. open shores, with/without vegetation) supported significantly different levels of reproduction activity. Management recommendations arising from this work are: (1) Expand the fishing ban during the reproduction season from the existing limited area (Beteha lagoons) to the entire littoral zone of the lake. (2) Maintain water levels higher than they currently are in order to allow greater availability of lagoon-type habitats. (3) Inundated vegetation should not be removed in an indiscriminant manner but selectively so as to create corridors and lagoon-like areas which are more favorable for reproduction.